Wing Dimorphism/polymorphism in True Bugs (Heteroptera) From a Functional Viewpoint: a Review.: Part I: Non-phytophagous Species - Gidó, Zsolt (Journal of Central European Green Innovation, 2023)
In this review article the available information on the wing dimorphism/polymorphism occurring at non-phytophagous Heteroptera is reviewed from a functional viewpoint. This meant practically the information about the wing dimorphism/polymorphism of the superfamily Gerroidea, as hardly anything has been published on this theme of other non-phytophagous Heteroptera. Seasonal and concurrent wing dimorphism/polymorphism are treated and discussed separately. Heritability and phenotypical plasticity of the wing form, and the effects of different modifying environmental factors are briefly reviewed and discussed. The superior reproductive ability of the non-macropterous form is well documented at female gerroid bugs; there are less available data on the males. The seasonal wing polymorphism directed by photoperiod and affected by temperature is usually well adapted to the current environmental conditions. The effects of the population density and that of the food quantity and quality on wing form of the gerroid bugs have not been well understood yet; and it is arguable, whether the macropterous/non macropterous ratio of the natural gerroid populations corresponds to the temporal stability of their actual habitats in an adaptive way. Wing dimorphism/polymorphism has to be evaluated within the wider concept of dispersal polymorphism, which includes other related phenomena like wing muscle polymorphism and behavioural differences.